After Arbeitsschutzkontrollgesetz. Strikes and organic intellectuals in the German meat industry - Daniela Ana; Ștefan Voicu (Sociologie Românească, 2023)
For decades, migrant workers with temporary and service contract work in the German meat industry have rarely been recruited by trade unions. The Arbeitsschutzkontrollgesetz (“Occupational Safety and Health Inspection Act”) law implemented in 2021 aimed to grant equal employment conditions to the majority of the workers in slaughterhouses, creating new avenues for trade unions to gain more members and organize industry-level negotiations for better wages and a collective agreement. This article explores the lessons we can draw from the series of strikes that accompanied the negotiations. By relying primarily on participant observation in the meat industry strikes and employing an actor-centred perspective on industrial relations, the paper reveals the role of shop-floor organic intellectuals in mobilizing and demobilizing workers. The analysis of the strikes shows that organic intellectuals can be instrumental in articulating the resistance of subaltern groups, but they can also be co-opted by dominant groups to manufacture consent.
Keywords: 300; meat industry; Romanians; migrant workers; organic intellectuals; trade union; strike; Germany